1995
DOI: 10.1016/s0008-6363(95)00137-9
|View full text |Cite
|
Sign up to set email alerts
|

Lazaroids and deferoxamine attenuate the intracellular effects of oxyhaemoglobin in vascular smooth muscle

Abstract: The present study provides results which are consistent with the hypothesis that the actions of haemoglobin on vascular smooth muscle are mediated by the formation of free radicals which subsequently affect intracellular calcium concentrations. This also implies that agents which impair free radical production or other processes leading to iron-catalyzed lipid peroxidation, are of potential value in cerebrovascular spasm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 0 publications
0
12
0
1
Order By: Relevance
“…This lazaroid compound is a potent antioxidant that inhibits lipid peroxidation in many models of oxidative stress. [33][34][35][36][37] Our data showed that U83836E significantly reduced hemoglobin neurotoxicity in a dose-dependent manner. Combination therapy using both U83836E and the broad-spectrum caspase inhibitor zVADfmk did not yield any additional protection.…”
Section: Discussionmentioning
confidence: 53%
“…This lazaroid compound is a potent antioxidant that inhibits lipid peroxidation in many models of oxidative stress. [33][34][35][36][37] Our data showed that U83836E significantly reduced hemoglobin neurotoxicity in a dose-dependent manner. Combination therapy using both U83836E and the broad-spectrum caspase inhibitor zVADfmk did not yield any additional protection.…”
Section: Discussionmentioning
confidence: 53%
“…Catalase or dimethyl sulfoxide (hydroxyl radical scavenger) afforded protection, but SOD only partially, and OH radicals reproduced these effects (67). Work with SMC cultures similarly revealed that contraction and intracellular Ca 2+ increase by oxyHb were attributable to the action of OH radicals (68,69).…”
Section: Hb and Free Radicalsmentioning
confidence: 99%
“…This value was chosen on the basis of prior experiments to set a tissue length in the optimal range for maximal force generation (Lo). 21 Viability was determined by maximal force response to high KCl (60 mmol/L).…”
Section: Tissue Preparationmentioning
confidence: 99%
“…21,22 Briefly, basilar arteries were isolated under sterile conditions and placed in a Petri dish containing Dulbecco's modified Eagle medium (DMEM). The vessels were cut into segments and the endothelium was removed mechanically.…”
Section: Cerebrovascular Smooth Muscle Cell Culturementioning
confidence: 99%